Raman Amplifier-Soliton Compressor and Its Application to All-Channel Hybrid OTDM Demultiplexing - Ismail, I; Matsuura, M; Kishi, N; Quang, NT (IEEE, 2024)
An all-optical demultiplexing of 40-Gb/s hybrid OTDM channels by using Raman-amplifier-soliton-compressor-flexible control-window is demonstrated. Error-free operations with less than 1.3-dB power penalties were obtained and this scheme is expected to be scalable toward higher bit-rates.